2021
DOI: 10.22146/ijc.62188
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and DFT Study of the Complexation of Schiff Base Derived Curcumin and L-Tyrosine with Al(III), Ag(I), and Pb(II) Metal Ions

Abstract: The multi-dentate Schiff base ligand (H2L), where H2L=2,2'-(((1,3,5,6)-1-(3-((l1-oxidaneyl)-l5-methyl)-4-hydroxyphenyl)-7-(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-diylidene)bis(azaneylylidene))bis(3-(4-hydroxyphenyl)propanoic acid), has been prepared from curcumin and L- Tyrosine amino acid. The synthesized Schiff base ligand (H2L) and the second ligand 1,10-phenanthroline (phen) are used to prepare the new complexes [Al(L)(phen)]Cl, K[Ag(L)(phen)] and [Pb(L)(phen)]. The synthesized compounds are charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Generally, the complexes were prepared by reacting the respective metal salts with the ligands using [Cur:M: (L-dopa)2] mole ratio, i.e. one mole of curcumin , one mole of metal salt and two mole of (Ldopa) [9] as the following equations:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the complexes were prepared by reacting the respective metal salts with the ligands using [Cur:M: (L-dopa)2] mole ratio, i.e. one mole of curcumin , one mole of metal salt and two mole of (Ldopa) [9] as the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…The Curcumin complexes of the Schiff Base [ (Curc )-L-Tyrosine] with Pb(II) , Al(III), and Ag(I) Ions constitute an especially interesting series of compounds. [9]. Complexation of curcumin with transition metals were synthesized, characterized and evaluated for various biological activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…56 Complexation of Schiff base derived curcumin and L-tyrosine with Al(III), Ag(I), and Pb(II) diamagnetic metal ions was studied experimentally and GIAO calculations supported the analysis of the observed NMR spectra. 57 Synthesis and experimental characteristics, supported by GIAO NMR calculations, on several novel pyrrole-3-ones 58 and 2-(piperidin-1-ylmethyl)-isoindoline-1,3-dione 59 were reported. An interesting study on mechanochemical synthesis of the catechol-theophylline cocrystal was reported.…”
Section: Dft Studies Of Nuclear Shieldingmentioning
confidence: 98%
“…Zn(II)-curcumin [37] Cu (II)--curcumin [38] , [39] Cr(III)--curcumin [40] Mixed ligand Schiff base with 1,10-phnanothroline, M= Co or Cu [41] Pd(II)-curcumin [42] M(diacetylcurcumin) 2 , where M= Cu(II) and Ni(II) [43] Ln=Eu(III) &La(III), rare earth -curcumin [44] M-curcumin, M=Cr(III),Mn(II), Fe(III), Co(II), Ni(II), Cu(II) ,Zn(II) [45] Mixed metal (Fe (II) &Cu(II)) -curcumin [46] Complexes of Curcuminoid-BF 2 [47] In acidic condition, Rosocyanine is produced as 2:1-complex from curcumin and boric acid [48] Curcumin-Fe(III) [49] Drug containing Rh(III) and curcumin (*Cp) ,*pentamethylcyclopentadienato [50] Fe(III)-curcumin [51] Prodrugs containing Co(III)-curcumin [52] Curcumin-2-aminophenol [53] Curcumin -Hg(II) complex in solution [54] Curcumin -M , M = Tc, Re [55] Mesoporous silica nanoparticles [56] Ga (III) -diketone (CUM)complex [57] (CUM)-based M(II) complexes as anticancer agents [58] DNA nanotechnology Cu(II)/Ni(II)/Zn(II)-curcumin-conjugated DNA complexes [59] cyclodextrins and conjugating it with silver nanoparticles [60] curcumin -Schiff base with various metal ions complexes ,M= Al(III), Mn(II), Fe(III), Co(II),Ni(II), Cu(II), Ag(I), Cd(II), Hg(II), and Pb(II) [61] Hexadentate (N 4 O 2 donor) Schiff base ligands derived from curcumin with some transition and non-transition metal cations [62] Schiff Base Derived Curcumin and L-Tyrosine with Al(III), Ag(I), and Pb(II) Metal Ions [63]…”
Section: Compounds Referencementioning
confidence: 99%